KEDUDUKAN BANK INDONESIA SEBAGAI BANK SENTRAL DALAM STRUKTUR KETATANEGARAAN INDONESIA - Sekar Anggun Gading Pinilih (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
The existence of Bank Indonesia as the central bank explicitly stated in the amendments to the Law of 1945 of Article 23D, which then further stipulated in Article 4 paragraph (2) of Law No. 23 of 1999 jo Law No. 4 of 2004 on Bank Indonesia. BI position as an independent state institution, so Bank Indonesia is not only acting on behalf of the state only, ie as the Central Bank, but also coordinate with other government implementers, such as the President who is in charge of government finances. Products issued by the central bank law should also see the first position of Bank Indonesia as anything. Bank Indonesia as an independent state institution acting on behalf of the state, then the Bank Indonesia Regulation is not included in the hierarchy of national legislation, but recognized and have binding legal force throughout ordered by legislation that is higher or established pursuant to the authority. However, in the case of implementing economic governance involving the cabinet, all products are technically coordinated law by the President through the Minister of Finance, so if the Bank Indonesia Regulation would be aligned with PP or other regulations, it must be submitted in advance to the President who is in charge of government finances.